2005
DOI: 10.1073/pnas.0408213102
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating lexical form, meaning, and structure in the neural language system

Abstract: A technique for studying the relationship between brain and language, which involves correlating scores on two continuous variables, signal intensity across the entire brains of brain-damaged patients and behavioral priming scores, was used to investigate a central issue in cognitive neuroscience: Are the components of the neural language system organized as a single undifferentiated process, or do they respond differentially to different types of linguistic structure? Differences in lexical structure, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 47 publications
7
56
0
Order By: Relevance
“…Behavioral tasks have included auditory same-different judgment , sentence completion (Patterson, Lambon Ralph, Hodges, & McClelland, 2001;Ullman et al, 1997) andpriming (Allen &Badecker, 2002;Longworth, Marslen-Wilson, Randall, & Tyler, 2005;Marslen-Wilson, Hare, & Older, 1993;Pastizzo & Feldman, 2002). A number of fMRI studies have also measured brain activation during priming or verb generation/repetition tasks (Joanisse & Seidenberg, 2005;Marslen-Wilson & Tyler, 1998;Tyler, Marslen-Wilson, & Stamatakis, 2005). In this paper we focus on the priming data.…”
Section: Behavioral Datamentioning
confidence: 98%
“…Behavioral tasks have included auditory same-different judgment , sentence completion (Patterson, Lambon Ralph, Hodges, & McClelland, 2001;Ullman et al, 1997) andpriming (Allen &Badecker, 2002;Longworth, Marslen-Wilson, Randall, & Tyler, 2005;Marslen-Wilson, Hare, & Older, 1993;Pastizzo & Feldman, 2002). A number of fMRI studies have also measured brain activation during priming or verb generation/repetition tasks (Joanisse & Seidenberg, 2005;Marslen-Wilson & Tyler, 1998;Tyler, Marslen-Wilson, & Stamatakis, 2005). In this paper we focus on the priming data.…”
Section: Behavioral Datamentioning
confidence: 98%
“…This aspect of grammar has been much studied because of the problems its dual regular/irregular structure presents for children during language acquisition. It has even been proposed that different brain areas become specialized for the processing of regular and irregular verbs (see, e.g., Tyler, Marslen-Wilson, & Stamatakis, 2005). The English past tense is of interest here because it is possible to simulate the emergent specialization of regular and irregular verbs to different pathways in an associative network (Thomas & Karmiloff-Smith, 2002;Thomas & Richardson, 2006).…”
Section: Example 3: the Emergence Of Specialized Functional Structurementioning
confidence: 98%
“…Increasing evidence suggests that inflectional morphology may be sensitive to the small neural changes observed in neurodegenerative disorders. The investigation of inflectional morphology has been used extensively to detect language impairment in numerous neurodegenerative disorders (Penke, 2008), and tested in several languages including English, French, Italian, and Hungarian (Nemeth et al, 2012;Pleh, Lukacs, & Racsmany, 2003;Teichmann et al, 2005;Tyler, Marslen-Wilson, & Stamatakis, 2005;Walenski, Sosta, Cappa, & Ullman, 2009). A recent study has shown that genetically tested individuals in the pre-symptomatic stage of Huntington's disease (pre-HD) already demonstrated language impairment on inflectional morphology, although none of the pre-HD individuals exhibited clinical or motor symptoms (Nemeth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%